Performance of a three-branch orthogonal polarization diversity scheme - Lukama, L; Konstantinou, K; Edwards, D; IEEE; IEEE; IEEE (2001)
The performance of a three-branch orthogonal polarization scheme consisting of one vertically polarized and two orthogonal horizontally polarized antennas at the receiver with a horizontally and vertically polarized transmitter is investigated. The paper shows that such a scheme provides diversity improvement of about 2dB more than the dual-branch system. Also the signals received at the three branches are highly uncorrelated. This scheme can make significant improvements in the link budget of a mobile network.